2023
DOI: 10.3390/s23031193
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Coronary Artery Disease Risk Prediction with Machine Learning Models

Abstract: The heart is the most vital organ of the human body; thus, its improper functioning has a significant impact on human life. Coronary artery disease (CAD) is a disease of the coronary arteries through which the heart is nourished and oxygenated. It is due to the formation of atherosclerotic plaques on the wall of the epicardial coronary arteries, resulting in the narrowing of their lumen and the obstruction of blood flow through them. Coronary artery disease can be delayed or even prevented with lifestyle chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…This study employed a total of six classification algorithms. Trigka et al [33] developed a stacking ensemble model after applying SVM, NB, and KNN with a 10-fold cross-validation synthetic minority oversampling technique (SMOTE) in order to balance out imbalanced datasets. This study demonstrated that a stacking SMOTE with a 10-fold cross-validation achieved an accuracy of 90.9%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study employed a total of six classification algorithms. Trigka et al [33] developed a stacking ensemble model after applying SVM, NB, and KNN with a 10-fold cross-validation synthetic minority oversampling technique (SMOTE) in order to balance out imbalanced datasets. This study demonstrated that a stacking SMOTE with a 10-fold cross-validation achieved an accuracy of 90.9%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this research work, the author [13] tested a number of machine learning (ML) models after using or not using the Synthetic Minority Oversampling Method (SMOTE), assessing and comparing their accuracy, precision, and recall. The stacking ensemble model using SMOTE with 10-fold cross validation outperformed the other models, with an accuracy of 90.9%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each student was equipped with a wireless single-channel Neurosky MindSet EEG headset. [26], which precisely measured cerebral activity over the frontal lobe. These students were tasked with watching a set of ten 2-minute-long videos.…”
Section: B Eeg Dataset Background and Descriptionmentioning
confidence: 99%
“…Each student is equipped with a wireless single-channel Neurosky MindSet EEG headset. [27], which precisely measured cerebral activity over the frontal lobe.…”
Section: Eeg Dataset Background and Descriptionmentioning
confidence: 99%